Influence of Substrate connection on dynamic-RON drift of 650 V packaged GaN HEMTs - M. Cioni; G. Giorgino; G. Cappellini; A. Chini; C. Miccoli; M.E. Castagna; A. Abbisogni; A. Contarino; F.A. Pizzardi; S. Smerzi; F. Iucolano (Power Electronic Devices and Components)
The impact of substrate connection on dynamic-RON degradation of 650 V packaged GaN HEMTs is investigated in this work. A custom setup is used to characterize the Devices Under Test (DUTs) under both static off-state stress and continuous switching stress. For both conditions, the Floating Substrate configuration showed larger RON-degradation with respect to the Grounded one, due to the back-gating effect experienced by the DUT when the Substrate terminal is not forced to ground. Furthermore, the impact of Drain-connected substrate is investigated, showing worse performance than Grounded and Floating configurations. This provides a physical explanation for the need to short-circuit Substrate and Source terminals under switch-mode operations.